Artificial Intelligence in HRM: A Scientometric Review of Global Publications - Judijanto, Loso (West Science Business and Management, 2025)
The integration of Artificial Intelligence (AI) into Human Resource Management (HRM) has triggered a significant transformation in how organizations attract, manage, and retain talent. This study aims to map the intellectual structure, thematic trends, and collaborative patterns of global research on AI in HRM using a scientometric approach. Drawing data from the Scopus database and utilizing VOSviewer software, the analysis covers co-authorship networks, institutional collaborations, keyword co-occurrences, temporal trends, and density distributions. The results reveal that core themes revolve around AI-enabled decision-making, employee engagement, job satisfaction, and performance enhancement, while strategic topics such as innovation, technology adoption, and sustainable development are gaining momentum. India, the United States, and Malaysia emerge as leading contributors, highlighting strong regional clusters and international partnerships. This study provides actionable insights for practitioners, outlines theoretical pathways for scholars, and identifies emerging areas that merit further investigation. It serves as a foundational reference for understanding the evolving intersection between AI technologies and HRM practices in the digital age.
Keywords: Artificial Intelligence; Human Resource Management; Scientometric Analysis; VOSviewer